Aplikasi Program Dinamik pada Metode Pelaksanaan Pengecoran Plat Lantai - Sedayu, Agung (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2010)
The development of world construction projects at this time that established by widespread methods of physical implementation which more excellent and sophisticated. The contractors are competing to obtain optimum results, and reduce losses more lower. The results obtained should not give benefit one person only, the other one should not to lose and suffer. Islam guides human how they work give benefit to their own and others. Many methods, equipment, and expertise deployed by the contractor for their work more optimal, one method for optimizing the physical implementation of the project is Dynamic Programming. Dynamic Programming to solve the problem optimization is not only with one step, but the events that took place linked to each other. Case study in this paper is the application of dynamic programming of implementation method of concrete casting on floor slab of Green House building, it’s belongs to Department of Biology, UIN Maliki Malang with backward induction phase. In modern century as this era has many fast-growing method of implementation that are categorized as advanced, but the problem that the methods actually optimal in terms of cost and time, due to cost and time parameters are very important in the progress of construction projects. The methods is very sophisticated so make project to be done very fast but it is very expensive financing, or the method is still conventional and traditional so that project costs will be reduced as cheaply, but the project need long time to be finished. Where is the decision that one will be expected to demand that we use what method. Mathematical formulas of dynamic programming as recursive equation with change big problem into smaller sub-problems, so the completion of smaller problems will be found solving of the original problem. Optimization process in this case that slab casting which solved in two methods, manually calculations with a recursive formula and use software DS Win 2.0. Optimization result of the two method are compared, and the two method produce similar results. Optimal or not parameter of the two method is optimum time and cost.